Randomised study of evolocumab in patients with type 2 diabetes and dyslipidaemia on background statin: Primary results of the BERSON clinical trial. Issue 6 (2nd April 2019) - Lorenzatti, Alberto J.; Eliaschewitz, Freddy G.; Chen, Yundai; Lu, Juming; Baass, Alexis; Monsalvo, Maria Laura; Wang, Nan; Hamer, Andrew W.; Ge, Junbo
Abstract : Aim: To evaluate the lipid‐lowering efficacy and safety of evolocumab combined with background atorvastatin in patients with type 2 diabetes mellitus (T2DM) and hyperlipidaemia or mixed dyslipidaemia. Materials and methods: BERSON was a double‐blind, 12‐week, phase 3 study (NCT02662569) conducted in 10 countries. Patients ≥18 to ≤80 years with type T2DM received atorvastatin 20 mg/d and were randomised 2:2:1:1 to evolocumab 140 mg every 2 weeks (Q2W) or 420 mg monthly (QM) or placebo Q2W or QM. Co‐primary endpoints were the percentage change in low‐density lipoprotein cholesterol (LDL‐C) from baseline to week 12 and from baseline to the mean of weeks 10 and 12. Additional endpoints included atherogenic lipids, glycaemic measures, and adverse events (AEs). Results: Overall, 981 patients were randomised and received ≥1 dose of study drug. Evolocumab significantly reduced LDL‐C versus placebo at week 12 (Q2W, −71.8%; QM, −74.9%) and at the mean of weeks 10 and 12 (Q2W, −70.3%; QM, −70.0%; adjusted P < 0.0001 for all) when administered with atorvastatin. Non‐high‐density lipoprotein cholesterol, apolipoprotein B100, total cholesterol, lipoprotein (a), triglycerides, high‐density lipoprotein cholesterol, and very low‐density lipoprotein cholesterol improved significantly with evolocumab versus placebo. The overall incidence of AEs was similar between evolocumab and placebo‐treated patients, and there were no clinically meaningful differences in changes over time in glycaemic variables (fasting serum glucose and HbA1c) between the two groups. Conclusions: In patients with T2DM and hyperlipidaemia or mixed dyslipidaemia on statin, evolocumab significantly reduced LDL‐C and other atherogenic lipids, was well tolerated, and had no notable impact on glycaemic measures.